Case report: Oncological surgery of the intraocular presentation of a transmissible venereal tumor in a dog (Revista Sistemas de Producción Agroecológicos, 2024)
Transmissible Venereal Tumor (TVT) is a contagious neoplasia with a global presence, transmitted mainly through sexual contact. This disease is characterized by primary lesions on the genitals, but it can also affect extra-genital areas. This report describes the case of a two-and-a-half-year-old male mixed-breed dog that was brought to the Veterinary Clinical Center of the University of Los Llanos due to changes in color and enlargement of its right eye. The owner mentioned that the dog had previously been diagnosed with TVT at another center, where it received treatment. Enucleation of the affected eye was chosen as the surgical intervention, followed by histopathological confirmation of TVT, leading to the initiation of chemotherapeutic treatment with vincristine at a dose of 0.025 mg/kg. After the surgery and chemotherapy sessions, the patient showed a satisfactory recovery.
Keywords: Enucleation; Eye; Metastasis; Neoplasm; TVT